Minat Beli Konsumen Terhadap Buah Melalui E-Commerce di Kota Bekasi - Vinanda, Gita; Rahmawati Putri Utami, Inayah (Program Studi Pengelolaan Agribisnis, 2025)
The development of information technology has led to the emergence of alternatives in consumption activities, one of which is online fruit purchase through e-commerce platforms, which is considered a potential solution. Ease of access and time efficiency are added values for consumers in obtaining horticultural products without having to visit physical stores. However, the level of consumer trust and purchasing interest in online fruit is still uneven, influenced by perceptions of freshness, quality, and product prices. This study aims to analyse the level of consumer interest in purchasing fruit sold online through e-commerce platforms and to identify the factors that influence it. The research was conducted in Bekasi City from June to July 2025 using a survey approach. The sampling technique used was accidental sampling, with a total of 450 respondents. The collected data were analysed using a quantitative descriptive analysis approach and multiple linear regression. The study findings indicate that the level of consumer purchasing interest is moderate. Additionally, the variables of price and product quality were found to have a significant impact on consumer purchasing interest, both simultaneously and partially. Keywords: E-Commerce, Fruit, Price, Product Quality